(3SO GdPQGFY aj LQGFe GdbJd (B:s (3OQGSI ebGQfI (B= Pretexts plugging in murder crimes : a comparative crimes /s - (3GdOQGhTI, eGLO SGdes ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3jJfGhd cJGH (B((3SO GdPQGFY aj LQGFe GdbJd(B) (3hGdPj bGe HJCdjag (B((3eGLO SGde GdOQGhTI(B) (3aj MhGdj (B(320) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3LQGFe GdbJd(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3bGYOI SO GdPQGFY aj GdTQjYI GdESdGejI, GdeHMK GdChd (B: (3eaghe SO GdPQGFY, GdeHMK GdKGfj (B: (3MLjI SO GdPQGFY aj GdTQjYI GdESdGejI, GdaUd GdKGfj (B: (3UdI bGYOI SO GdPQGFY HeBdGJ GdCaYGd hebGUO GdTQjYI GdESdGejI, GdeHMK GdChd (B: (3UdI bGYOI SO GdPQGFY HeHOC GdfXQ aj eBdGJ GdCaYGd, GdeHMK GdKGfj (B: (3UdI bGYOI SO GdPQGFY HebGUO GdTQjYI GdESdGejI, GdeHMK GdKGdK (B: (3GdfaS GdHTQjI (B: (3JYQjagG hecGfJgG, GdaUd GdKGdK (B: (3LQGFe GdbJd hSO PQGFYgG aj GdTQjYI GdESdGejI, GdeHMK GdChd(B: (3LQGFe GdbJd aj GdTQjYI GdESdGejI, GdeHMK GdKGfj (B: (3JWHjbGJ bGYOI SO GdPQGFY aj efY LQjeI GdbJd, Ke GfJgi HbGFeI GdeUGOQ(B.s
(3JUeje hEfJGL (B: (3ecJH OGQ GdKbGaI ddJUeje hGdEfJGL(B.s
(3CUd gPG GdcJGH eGLSJjQ HETQGa GdOcJhQ eMeO QGcGf GdOZej aj LGeYI Bd GdHjJ(B-(3GdCQOf(B.s
(3HHdjhLQGajI (B: (3UaMI (B303-320.s
Keywords: (3GdbUGU (B((3abg ESdGej(B)s; (3LQGFe GdbJd (B((3abg ESdGej(B)s; (3LQGFe GdbJds -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs